Underwriter’s impact on the IPO process : How do the bank’s interests align with the issuer’s objectives? - Haapasaari, Juhana (My University, 2024)
This thesis examines the initial public offering (IPO) process of companies and the role that underwriters have as participants in making a private company public. Listing shares on the public markets is a significant decision in a company’s life cycle. The process of conducting an IPO is one of the most common ways to list shares on the public markets and raise external equity. The process usually includes several working parties, but this thesis will narrow down the examination to the underwriter’s role and contribution. The underwriter is usually known as the leading participant in the offering, and the role involves many responsibilities essential to executing this process. Typically, an investment bank acts as the underwriter and views the issuing company as its client. The main responsibilities of the underwriter can be divided into operations before and after the shares are listed on the public markets. This thesis emphasizes the pre-market entry activities conducted by the bank, which include valuing the company, carrying out various marketing tasks, pricing the shares, and allocating the shares to the investors. Appointing an underwriter as part of the initial public offering has become almost a self-evident stage, reaching a point of being nearly a norm when planning to list shares on the public markets. However, the underwriter also has its own interests and objectives in the process, which may not always align with those of the issuer, and this topic has gotten relatively little attention in the previous literature. One of the widely researched phenomena in the IPO literature is the effect of underpricing the issued shares compared to their fair value. Also, the decisions made in allocation policies that favour certain investors are among the most relevant issues in the process. This thesis aims to bring new angles to these commonly known effects, while enlightening the motives of the issuer and the underwriter, as well as their relationship. The thesis analyzes the interests present in the pricing and allocation decisions made by the investment bank. The paper also aims to conclude how the underwriter’s actions and behavioural tendencies align with the issuer’s objectives. The study is conducted in the form of a literature review, where the conclusions are mostly based on scientific articles and books relevant to the subject. Empirical evidence is also included to support and strengthen the findings. The conclusion of the thesis suggests that the underwriting entity facilitates many actions and provides an experienced platform for the offering, while in some cases bearing the risk of a failed offer. However, the pricing and allocation decisions include behaviour that may indicate the bank advancing its own interests at the issuer’s expense. The underpricing phenomenon is usually not considered to be in the best interest of the issuer, but the underwriter still encourages this effect through its own actions to favour the investors and pursue its own goals. The discretionary allocation policies of the investment bank have also been prone to favour institutional investors and regular clients, which may result in not serving the issuer’s interests. The findings in the thesis, however, suggest that issuers are partially passively accepting these actions made conflicting with their interests due to some noted benefits and the financial losses from the underpricing being relatively modest.

Tässä tutkielmassa tarkastellaan yritysten listautumisannin (IPO) prosessia ja roolia, joka pääjärjestäjillä on osallisina yksityisen yrityksen tekemisessä julkiseksi. Listautuminen julkisille markkinoille on merkittävä päätös yrityksen elinkaaressa. IPO-prosessi on yksi yleisimmistä tavoista listata osakkeita julkisille markkinoille ja hankkia ulkopuolista omaa pääomaa. Prosessi sisältää yleensä useita toimijoita, mutta tämä tutkielma rajaa tarkastelun pääjärjestäjän rooliin ja kontribuutioon. Pääjärjestäjä tunnetaan yleensä johtavana osallisena listautumisannissa, ja rooliin kuuluu monia tämän prosessin kannalta olennaisia vastuita. Yleensä pääjärjestäjänä toimii investointipankki, joka näkee liikkeeseenlaskijan asiakkaanaan. Pääjärjestäjän vastuut voidaan jakaa toimintoihin ennen osakkeiden listaamista julkisille markkinoille ja sen jälkeen. Tämä tutkielma painottuu pankin aktiviteetteihin ennen markkinoille tuloa, joihin kuuluu yrityksen arvon määrittäminen, erilaisten markkinointitehtävien toteuttaminen, osakkeiden hinnoittelu ja osakkeiden allokointi sijoittajille. Pääjärjestäjän nimeämisestä osaksi listautumisantia on tullut melkein itsestään selvä vaihe, joka on käytännössä vakiintunut lähes normiksi suunniteltaessa osakkeiden listaamista julkisille markkinoille. Pääjärjestäjällä on kuitenkin myös omat intressinsä ja tavoitteensa prosessissa, jotka eivät aina välttämättä ole linjassa liikkeeseenlaskijan etujen kanssa, ja tämä aihe on saanut suhteellisen vähän huomiota aikaisemmassa kirjallisuudessa. Eräs laajalti tutkituista ilmiöistä listautumisantien kirjallisuudessa on liikkeeseen laskettujen osakkeiden alihinnoittelu suhteessa niiden käypään arvoon. Myös päätökset, jotka tehdään osakkeiden allokointikäytännöissä suosien tiettyjä sijoittajia, ovat prosessin tärkeimpiä aiheita. Tämä tutkielma pyrkii tuomaan uusia näkökulmia näihin tunnettuihin ilmiöihin, samalla valaisten liikkeeseenlaskijan ja pääjärjestäjän motiiveja sekä niiden keskinäistä suhdetta. Tutkielma analysoi investointipankin tekemissä hinnoittelu- ja allokointipäätöksissä esiintyviä intressejä. Tutkielmassa pyritään myös selvittämään, miten pääjärjestäjän toimet ja taipumukset ovat linjassa liikkeeseenlaskijan tavoitteiden kanssa. Tutkimus on toteutettu kirjallisuuskatsauksena, jossa johtopäätökset perustuvat pääosin aiheeseen liittyviin tieteellisiin artikkeleihin ja kirjoihin. Empiirisiä havaintoja on myös lisätty tukemaan ja vahvistamaan tutkimustuloksia. Tutkielman johtopäätöksenä todetaan, että pääjärjestäjä mahdollistaa monia toimintoja ja tarjoaa kokeneen alustan listautumiselle, toisinaan kantaen riskin epäonnistuneesta annista. Hinnoittelu- ja allokointipäätökset sisältävät kuitenkin käyttäytymistä, joka voi viitata siihen, että pankki ajaa omia etujaan liikkeeseenlaskijan kustannuksella. Alihinnoittelu-ilmiön ei yleensä katsota olevan liikkeeseenlaskijan edun mukaista, mutta pääjärjestäjä kuitenkin edistää tätä vaikutusta omilla toimillaan sijoittajien ja omien tavoitteidensa hyväksi. Investointipankin harkinnanvaraiset allokointikäytännöt ovat myös olleet taipuvaisia suosimaan institutionaalisia sijoittajia ja säännöllisiä asiakkaita, mikä voi johtaa liikkeeseenlaskijan intressien laiminlyöntiin. Opinnäytetyön havainnot kuitenkin viittaavat siihen, että liikkeeseenlaskijat hyväksyvät osittain passiivisesti nämä intressiensä vastaiset toimet, koska niihin liittyy tiettyjä havaittuja hyötyjä ja alihinnoittelusta aiheutuvat taloudelliset menetykset ovat suhteellisen maltillisia.
Keywords: nitial public offering (IPO), underwriter, issuer, pecking order theory, principal– agent theory, underpricing, oversubscription, winner’s curse theory, signalling theory